Australia needs to increase testing to achieve hepatitis C elimination. Issue 8 (13th March 2020) - Scott, Nick; Sacks‐Davis, Rachel; Wade, Amanda J; Stoove, Mark; Pedrana, Alisa; Doyle, Joseph S; Thompson, Alexander J; Wilson, David P; Hellard, Margaret E
Abstract: Objectives: To assess progress in Australia toward the 2030 WHO hepatitis C elimination targets two years after the introduction of highly effective direct‐acting antiviral (DAA) treatments. Design: Analysis of quarterly data on government‐subsidised hepatitis C RNA testing and hepatitis C treatment in Australia, January 2013 – June 2018. Changes in testing and treatment levels associated with DAA availability were assessed in an autoregressive integrated moving average (ARIMA) statistical model, and the impact by 2030 of different levels of testing and treatment were estimated using a mathematical model. Major outcome measures: Hepatitis C prevalence among people who inject drugs; annual hepatitis C incidence relative to 2015 levels; projections for the hepatitis C care cascade in 2030. Results: The mean annual number of treatments initiated for people with hepatitis C increased from 6747 during 2013–2015 (before the introduction of DAAs) to 28 022 during 2016–18; the mean annual number of diagnostic RNA tests increased from 17 385 to 23 819. If current trends in testing and treatment continue (ie, 2018 testing numbers are maintained but treatment numbers decline by 50%), it is projected that by 2030 only 72% of infected people would be treated (by 2025 all people diagnosed with hepatitis C would be treated). The incidence of hepatitis C in 2030 would be 59% lower than in 2015, well short of the WHO target of an 80% reduction. The identification and testing of people exposed to hepatitis C must be increased by at least 50% for Australia to reach the WHO elimination targets. Conclusion: Hepatitis C elimination programs in Australia should focus on increasing testing rates and linkage with care to maintain adequate levels of treatment.